(untitled) (Revista Peruana de Investigación Educativa, 2022)
In Peru, there are about 1 million adolescents living in rural areas, who, face different economic, social and educational problems (INEI, 2027). However, there are few studies that relate the subjective well-being of these adolescents and their education in rural schools. In this sense, the objective of this study was to analyze the factors that promote subjective well-being in adolescents from rural schools in Peru. In addition, another analysis is carried out to observe the moderating effect of the relationship at the individual level (support from an adult and sense of relevance among peers) with the climate and school violence on the subjective well-being of adolescents in rural areas. The sample consisted of 2574 students from the three rural educational service models (Secundaria Tutorial, Alternancia y Residencial) from 12 to 18 years (M = 14.64). The results show that the students of the three educational models experience high levels of well-being (<98 %), with Secundaria tutorial being the model that reports the highest level of index. Finally, in relation to the effects of school violence on the subjective well-being of rural adolescents, it is found that bullying significantly affects their subjective well-being in the three rural educational models, while the results of the moderating effect show that both the Bullying and peer support has a determining effect on the student’s well-being with his life in general.